Oerskovia xanthineolytica bacteremia with hypernatremic seizure in an infant with severe pneumonia: an uncommon but life threatening disease treated in a critical care ward in Bangladesh - Sharifuzzaman, -; Chisti, Mohammod Jobayer; Ahmed, Dilruba; Wahid, Syeda Umme Habiba; Sadique, Tuhin; Mazumder, Razib; Hossain, Mohammad Anowar; Chowdhury, Nusrat Jahan; Maruf, Abdullah Al (Bangladesh Critical Care Journal, 2016)
A 8 months old mildly underweight baby girl was initially admitted at the Short Stay Ward of Dhaka hospital of icddr,b with acute watery diarrhea. On the next day she was transferred to Intensive Care Unit (ICU) of the same hospital for convulsion. After exclusion of potential differentials of convulsion, hypernatremia was added as new problem. She was treated for AWD and hypernatremic convulsion at the ICU following standard hospital protocol. She had also found to have pneumonia (confirmed by radiological evidence) which eventually improved with second line of antibiotics. Finally she found to have Oerskovia xanthineolytica bacteremia which was improved with the ongoing treatment of pneumonia. We report Oerskovia xanthineolytica bacteremia as the 1st case in Bangladesh. Bangladesh Crit Care J March 2016; 4 (1): 38-40